Environmental impact assessment of a cocoa shell pellet (CSP) combustion system: Effects of integrating an emission filtration system - A. D. Rincon-Quintero; Zirley Dayana Ardila-Caballero; Mauricio Ruiz-Ochoa; Camilo Leonardo Sandoval-Rodriguez; Luis Alfonso Del Portillo-Valdes (Heritage and Sustainable Development)
Densified biomass in the form of pellets, made from cocoa shell pellet (CSP), represents a renewable thermal energy source. Experimental combustion tests and emission readings were then conducted over 15 minutes, both with and without the filter, resulting in significant average improvements; with CO levels decreasing from 1710 to 475 ppm, CO2 levels dropping from 2.13% to 0.2%, H2S levels reducing from 39.36 to 5.7 ppm, and N2 decreasing from 76.64% to 74.71%. O2 levels increased from 15.06% to 17.02%. This assessment showed a modification of environmental impact assessment with the installation of the filtration system, reducing the negative impacts from 18 to 13. It changed from a medium-impact project (without filter) to a low-impact project (with filter), demonstrating the capacity of the filter prototype to improve the environmental conditions of the surroundings. In addition, the potential energy was determined according to ASTM D4809-13, obtaining a higher heating value of up to 15.5 MJ/kg, thereby ensuring the efficient implementation of a combustion chamber with thermal storage that transfers heat to a forced-air drying system for food, replacing the use of fossil fuels in this methodology. The use of these compact drying systems involves the generation of emissions of O2, CO, CO2, N2, and H2S. Therefore, monitoring of these emissions is conducted using a gas analyser.